Nanomechanical force mapping of restricted cell-to-cell collisions oscillating between contraction and relaxation - Hu, Benhui (2020)
Contact-mediated cell migration strongly determines the invasiveness of the corresponding cells, collective migration, and morphogenesis. The quantitative study of cellular response upon contact relies on cell-to-cell collision, which rarely occurs in conventional cell culture. Herein, we developed a strategy to activate a robust cell-to-cell collision within smooth muscle cell pairs. Nanomechanical traction force mapping reveals that the collision process is promoted by the oscillatory modulations between contraction and relaxation and orientated by the filopodial bridge composed of nanosized contractile machinery. This strategy can enhance the occurrence of cell-to-cell collision, which renders it advantageous over traditional methods that utilize micropatterned coating to confine cell pairs. Furthermore, modulation of the balance between cell tugging force and traction force can determine the repolarization of cells and thus the direction of cell migration. Overall, our approach could help to reveal the mechanistic contribution in cell motility and provide insights in tissue engineering.